2022
DOI: 10.2147/jir.s366246
|View full text |Cite
|
Sign up to set email alerts
|

Thrombo-Inflammatory Prognostic Scores Improve BISAP-Based Risk Stratification in Acute Pancreatitis Patients: A Retrospective Cohort Study

Abstract: Purpose The thrombo-inflammatory prognostic score (TIPS) and the bedside index for severity in acute pancreatitis (BISAP) are both scoring systems that enable the rapid prognostic assessment of early-stage acute pancreatitis (AP) patients, but the overall prognostic utility of these individual systems is limited. This study was thus developed to explore whether a combination of TIPS and BISAP scores would offer better insight to facilitate the risk stratification of AP patients. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In previous research, we showed that the thrombo-inflammatory scoring system, which integrates basic thrombus and inflammatory indicators, contributed to the risk classification for aortic dissection, sepsis, and pancreatitis ( Li et al, 2015 , 2017a , 2018 , 2020 ; Han et al, 2022a , b ). In this multicenter retrospective cohort research of patients from the Retrospective Multicenter Study for Ischemic Stroke Evaluation (REMISE) study, we evaluated the hypothesis that a novel thrombo-inflammatory predictive scoring system (TIPS), consisting of a thrombotic and an inflammatory biomarker, could stratify patients with IS on their risk for SAP at the time of admission.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, we showed that the thrombo-inflammatory scoring system, which integrates basic thrombus and inflammatory indicators, contributed to the risk classification for aortic dissection, sepsis, and pancreatitis ( Li et al, 2015 , 2017a , 2018 , 2020 ; Han et al, 2022a , b ). In this multicenter retrospective cohort research of patients from the Retrospective Multicenter Study for Ischemic Stroke Evaluation (REMISE) study, we evaluated the hypothesis that a novel thrombo-inflammatory predictive scoring system (TIPS), consisting of a thrombotic and an inflammatory biomarker, could stratify patients with IS on their risk for SAP at the time of admission.…”
Section: Introductionmentioning
confidence: 99%